Logits Models of Corporate Bankruptcy Prediction for the UK Public Companies - LIN, YUE (2017)
The main purpose of the study is to develop a reliable bankruptcy prediction model for UK public companies because UK companies are playing increasingly important role in global economy. Logit Models are employed as a tool to analyze financial ratios for the companies and data of companies are from 2008 to 2017. The results indicate that Univariate Logit Model and Multinomial Logit Model are better than Multivariate Logit Model in predicting bankruptcy in term of more significant predictors; as the year more close to failure, predictive power of the ratios will be stronger. In short, although the study has extended previous studies in some aspects, further researches should be taken in the future to complete the bankruptcy prediction models.